Analisis Frase “Kaki Rusa” dan Implementasinya Berdasarkan 2 Samuel 22:34; Mazmur 18:33; dan Habakuk 3:19 - Aska Aprilano Pattinaja; Andris Kiamani (Kharisma: Jurnal Ilmiah Teologi, 2026)
Abstract The phrase “deer's legs” appears three times in 2 Samuel 22:34; Psalm 18:33; and Habakkuk 3:19. The purpose of this study is to analyze the precise meaning of this phrase. In reviewing the literature, scholars' interpretations of this phrase vary, ranging from a symbol of military prowess, a metaphor for the journey of faith, the cosmological framework of the Ancient Near East, faith in the midst of suffering, and the ethical dimension in human relations with creation through a zoomorphic approach. Based on a study of literature and hermeneutics, this study finds three meanings for this phrase: First, dependence on God; Second, divine enabling power; Third, faith that endures in crisis. This study is very important and serves as a reference for teachers and preachers so that they can convey the truth, especially regarding the phrase “deer's feet.” AbstrakFrase “kaki rusa” muncul tiga kali dalam 2 Samuel 22:34; Mazmur 18:33; dan Habakuk 3:19. Tujuan penelitian ini adalah menganalisis apa makna yang tepat untuk menjelaskan frase ini dengan tepat. Dalam penelusuran litertaur penafsiran para sarjana mengenai frase ini bermacam-macam, mulai dari simbol kecakapan militer, metafora perjalanan iman, kerangka kosmologi Timur Dekat Kuno, iman di tengah penderitaan dan dimensi etis dalam relasi manusia dengan ciptaan melalui pendekatan zoomorfisme. Berdasarkan metode studi literatur dan hermeneutik, maka penelitian ini menemukan 3 makna dari frase ini yakni: Pertama, ketergantungan pada Allah; Kedua, kekuatan ilahi yang memampukan; Ketiga, iman yang bertahan dalam krisis. Penelitian ini sangat penting dan menjadi rujukan bagi para pengajar dan pengkhotbah agar dapat menyampaikan kebenaran khususnya mengenai frase “kaki rusa.”